2009
DOI: 10.1088/0004-637x/700/2/1233
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse X-Ray Emission in Globular Cluster Cores

Abstract: The unresolved X-ray emission in the cores of 10 globular clusters hosting millisecond pulsars is investigated. Subtraction of the known resolved point sources leads to detectable levels of unresolved emission in the core region of M28, NGC 6440, M62, and NGC 6752. The X-ray luminosities in the 0.3-8 keV energy band of this emission component were found to lie in the range ∼1.5 × 10 31 erg s −1 (NGC 6752) to ∼2.2 × 10 32 erg s −1 (M28). The lowest limiting luminosity for X-ray source detections amongst these f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Eger et al (2010) and Wu et al (2014) identify likely diffuse emission from the outskirts of Terzan 5 and 47 Tuc, but the flux is <10% of the total from these clusters, and is not attributed to the kind of point sources we study, so we do not include it. Hui et al (2009) do not find evidence for diffuse X-ray emission in Chandra observations of the globular clusters M5, M13, M3, M71, M53, and M4. On the other hand, Bassa et al (2004) find roughly equal L X from M4's core below L X (0.5-2.5)= 6×10 30 ergs/s, vs. sources from 6×10 30 up to = 6×10 31 erg/s, indicating that unresolved emission can produce a significant contribution in the analysis of X-ray faint clusters.…”
Section: Globular Clustersmentioning
confidence: 56%
“…Eger et al (2010) and Wu et al (2014) identify likely diffuse emission from the outskirts of Terzan 5 and 47 Tuc, but the flux is <10% of the total from these clusters, and is not attributed to the kind of point sources we study, so we do not include it. Hui et al (2009) do not find evidence for diffuse X-ray emission in Chandra observations of the globular clusters M5, M13, M3, M71, M53, and M4. On the other hand, Bassa et al (2004) find roughly equal L X from M4's core below L X (0.5-2.5)= 6×10 30 ergs/s, vs. sources from 6×10 30 up to = 6×10 31 erg/s, indicating that unresolved emission can produce a significant contribution in the analysis of X-ray faint clusters.…”
Section: Globular Clustersmentioning
confidence: 56%
“…Observations of globular clusters with accompanying X-ray haloes support this idea (Mirabal 2010). In addition, it has been suggested by Hui et al (2009) that while the luminous X-ray pulsar wind nebulae have been detected from pulsars in the Galaxy, there is no evidence of a contribution to the diffuse X-ray emission by pulsar wind nebulae within globular clusters. Searching for low and high energy diffuse emission within and around pulsar-hosting globular clusters could, in principle, help uncovered the heating structures from these objects and provide a much clearer understanding of the underlying processes at work.…”
Section: Discussionmentioning
confidence: 95%
“…The γ-ray emission from GCs shows some interesting correlations with the GC content. For example, Abdo et al [6] and Hui et al [187] find a clear correlation of the observed GeV γ-ray luminosity with the stellar encounter rate which determines the number of MSPs and Cataclysmic Variables within the specific GC. It is believed that the encounter rate determines the formation rate of compact binaries which are responsible for the origin of the MSPs inside GCs.…”
Section: Gamma-ray Observationsmentioning
confidence: 99%
“…The encounter rate can be estimated from the observed density of stars in the core of GC and the core radius [166]. Moreover, Hui et al [187] report the positive correlation of the γ-ray luminosity with the metallicity [Fe/H] of the GC. They also find a tendency of the correlation of the γ-ray flux with the energy density of soft photon field at the GC location.…”
Section: Gamma-ray Observationsmentioning
confidence: 99%